Harnessing Filaria for Diabetic Foot Cellulitis-A Unique Case Report - Shankar, Kakaraparthy Ravi; Gnaneswari, Kodi; Devi, Siriki Thirumala (Indian Journal of Pharmacy Practice)
Diabetic foot cellulitis is a chronic complication of diabetes mellitus leading to chronic infections, delayed healing, and in several severe cases amputation. The conventional treatment with antibiotics may not be very effective and there is an immediate need to explore the alternative treatment approaches for the effective treatment of Diabetic foot cellulitis. The most frequent causative organisms responsible for Diabetic foot cellulitis are Staphylococci, Streptococci and Pseudomonas species. Even though there are several factors predisposed to this infection and are probably operative in the pathogenesis of illness, how these factors predispose patients to Diabetic foot cellulitis is completely not known. Filarial infections have been known to modulate host immune responses particularly anti-inflammatory cytokines, like Interleukin-10 which may contribute to controlled immune response and reduced tissue damage. This could suggest a possible interplay between filarial infections and Diabetic foot cellulitis.
Keywords: Diabetic foot cellulitis; Amputation; Causative organisms; Antibiotic therapies; Inflammation; Filaria; Blisters